IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER DI SMK MUHAMMADIYAH 1 MERTOYUDAN - Yongki Agus Prasetyo (Jurnal Pendidikan Vokasi Otomotif, 2019)
The purpose of this research is to find the implementation of improved character education (PPK) at SMK Muhammadiyah 1 Mertoyudan. The indicator in this research include planning, carrying out, and evaluating a PPK Program at SMK Muhammadiyah 1 Mertoyudan. This research is a case study with a quantitative descriptive method approach. The study shows the implementation of improved character education in SMK Muhammadiyah 1 Mertoyudan a good category with a 76,26% amount of application. The results include some indicator of a 79,97% PPK plan, 77,41% implementation of PPK, and 71,59% evaluation. In the process of planning the PPK program involves all the school equipment. For performance of the PPK through the learning process, extracurricular activities, and the school’s example of this it. The high point of attachment in the PPK on learners of 76,54% in both categories. The PPK evaluation process whole school kit took part and follow up corrected some of the missing components.